Clinicoetiological Study of Epilepsy in Children Presenting To Speciality Epilepsy Clinic at Tertiary Medical Hospital - Parekh, Zankhana R.; Joshi, Umesh; Vora, Nitish; Shah, Aasheeta (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Objectives: To identify the clinical & etiological profile of children and the characteristics of seizures in them along with therapeutic response. Subjects and Methods: All patients who attended the Epilepsy Clinic & fulfilled the selection criteria were enrolled in study. This is a descriptive study of 18 months & involved analysis of records of the patients who came to specialty OPD. Three groups were formed accordingly - focal, generalized & unknown onset with further etiological sub-divisions -Genetic, Structural/Metabolic, Immune, Infectious & Unknown. Results: In all, 417 patients were studied. The distribution as per clinical presentation was- group I (generalized) 215(58.5%) - group II (focal) 154(36.9%), group III (unknown) 48(4.6%). The main etiologies were perinatal asphyxia (28.3%) NHBI (11.4%) in (structural-metabolic) sub group. In Genetic & Infectious, Channelopathies (10.5%) & Post Meningitis Sequelae (4.7%)were main etiology. 56.3% of the patient in group II were on more than 3 AEDs. 14.3% in group I were weaned of AEDs. 61.4% patients in group II were having neurodevelopmental Sequelae. EEG revealed abnormal activity in 30(6.2%) in group I & 31(19.3%) in group II. Maximum patient with refractory epilepsy were seen in group III. Conclusion: To have a good management of epilepsy we need to have multi-dimensional classification of epilepsy based on both clinical & etiological spectrum. Perinatal Asphyxia & NHBI are one of the most common yet avertible etiologies.